Complete chloroplast genome sequence of Pedicularis verticillata and chloroplast genome reconstruction of P. cheilanthifolia (Orobanchaceae). Issue 2 (2nd April 2020) - Cho, Won-Bum; Han, Eun-Kyeong; Choi, Hyeok Jae; Lee, Jung-Hyun
Abstract: We here report the complete chloroplast genome of Pedicularis verticillata and the reconstructed chloroplast genome of Pedicularis cheilanthifolia, the first such genome reported for this genus. The P. verticillata genome is 142, 733 bp, including a 24, 984-bp inverted repeat (IR) region, 89, 723-bp large single-copy (LSC) region, and 12, 042-bp small single copy (SSC) region, and the P. cheilanthifolia genome is 147, 807 bp (IRs: 24, 916 bp; LSC: 82, 718 bp; SSC: 15, 257 bp). The chloroplast genome of P. verticillata contains 116 genes, including 71 coding genes, 8 rRNAs, and 37 tRNAs. In the genomes of both species, 10 ndh genes are lost and ndh B was identified in the IR region. Additionally, rps 16 is also lost in P . verticillata but not in P . cheilanthifolia . The maximum-likelihood phylogenetic tree showed that Pedicularis is a monophyletic and sister group to other hemi-parasitic species in Orobanchaceae.